INFLUENCE OF CRITERIA USED IN ALLOCATION AND DISBURSEMENT OF SECONDARY EDUCATION CONSTITUENCY DEVELOPMENT BURSARY FUND ON RETENTION OF STUDENTS FROM VULNERABLE BACKGROUND IN PUBLIC SCHOOLS IN KIMININI SUB-COUNTY, KENYA - Christabel , Nafula W.; Kikechi, Ronald Werunga (IJRDO- Journal of Educational Research, 2023)
The Secondary Education Constituency Bursary Fund (SECBF) was created to enhance high school enrollment and retention among the underprivileged and other vulnerable groups; however, there have been several concerns about some kids leaving school early. Thus, the purpose of the study was to evaluate the influence of criteria used in allocation and disbursement of SECBF on retention of students from vulnerable background in public secondary schools in Kiminini sub-county, Kenya. It adopted a descriptive survey research design, with a target population of 333 persons including 109 parents, 109 Principals/head teachers in secondary schools, 6 members of the CDF committee, and 109 beneficiaries. The sample size of 182 persons was determined using the Krejcie & Morgan table (1970). The researcher collected data using questionnaires and interview guides. The instruments were validated by experts in the area of study. Reliability of the instruments was determined through a pilot study where Spearman’s rank correlation coefficient (r) was analyzed for the two scores and found to be 0.78, which implied that the instruments were reliable. Quantitative data was analyzed using descriptive and inferential statistics and presented in tables, while qualitative data analyzed in themes and sub themes and presented using quotations. The study established that Secondary Education Constituency Bursary Fund practices such as criteria used in allocation and disbursement significantly (p=0.000) influence retention of students from vulnerable background in public secondary schools. It was therefore recommended that there should be a consideration of criteria used in allocation and disbursement, public awareness, proportion allocated and consistency in allocation and disbursement as this will enhance retention of students from vulnerable background in public secondary schools. The information provided by this research will benefit policymakers, community members and academicians.